Understanding the Role of Teacher Immediacy in Enhancing English Communication among University Learners - Sengkey, Virginia Gabrella (Institut Agama Islam Negeri Palopo, 2025)
This study utilized both correlational and comparative research methodologies to investigate the relationship between teacher immediacy behaviors and university students’ willingness to communicate (WTC) in English classes, as well as to assess potential gender- based differences in students’ perceptions of these behaviors and their WTC of a private university in North Sulawesi. The sample consisted of 275 undergraduate university students enrolled in English courses, ranging from basic to advanced English levels. The analysis revealed a statistically significant correlation between teacher immediacy behaviors and students' WTC in English classes, with a p-value of .000 and r = 0.392. Furthermore, the results indicated no significant gender differences in students’ perceptions of teacher immediacy behaviors or their WTC in English classes. Therefore, cultivating a warm, non-threatening classroom climate where students feel emotionally safe can further amplify the benefits of teacher immediacy and promote greater participation in English communication tasks.